2005
DOI: 10.1103/physrevb.72.245407
|View full text |Cite
|
Sign up to set email alerts
|

Role of van der Waals interactions in adsorption of Xe on Cu(111) and Pt(111)

Abstract: We consider some recently developed schemes for treating van der Waals interactions within the density functional theory ͑DFT͒ on the widely discussed example of adsorption of Xe on Cu͑111͒ and Pt͑111͒ surfaces. Consistent with the overall weakness of the Xe surface and Xe-Xe interactions we assess the performance of the schemes that are appropriate to systems consisting of nearly isolated fragments in which the coefficients of the van der Waals expansion are deduced from DFT calculations. Such generalized DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 33 publications
2
63
0
Order By: Relevance
“…Another test that LDA gives right numbers for wrong reasons can be easily done by shifting the graphene layer away from the Ir surface and noticing that the standard asymptotic dependence of the van der Waals layer-surface attraction energy is not reproduced. Also, by inspecting the curvature of the adsorption energy minimum and comparing it with experimental values shows that LDA does not give the correct result [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…Another test that LDA gives right numbers for wrong reasons can be easily done by shifting the graphene layer away from the Ir surface and noticing that the standard asymptotic dependence of the van der Waals layer-surface attraction energy is not reproduced. Also, by inspecting the curvature of the adsorption energy minimum and comparing it with experimental values shows that LDA does not give the correct result [28,29].…”
Section: Resultsmentioning
confidence: 99%
“…in particular, for Xe a general tendency is found [6,[8][9][10][11] for adsorption on metallic surfaces in the low-coordination top sites (this behavior is attributed [6,16] to the delocalization of charge density that increases the Pauli repulsion effect at the hollow sites relative to the top site and lifts the potential well upwards both in energy and height).…”
Section: Introductionmentioning
confidence: 99%
“…We chose the PBE [44] reference DFT functional, which is probably the most popular GGA functional. The problem of choosing the optimal DFT functional, particularly in its exchange component, to be combined with long-range vdW interactions and the related problem of completely eliminating double counting of correlation effects still remain open [19]; however they are expected to be more crucial for adsorption systems characterized by relatively strong adparticle-substrate bonds ("chemisorption") and, for instance, for the determination of the perpendicular vibration frequency [11] than for the equilibrium properties of the physisorbed systems we focus on in our paper.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors attributed the on-top site preference to charge polarization of both the Xe atom and underlying noble or transition metal (TM) atom as a consequence of the Pauli repulsion. Lazić et al [20] reported the results of potentials between a Xe and the substrate using the GGA with an intra-fragment treatment of the vdW interaction for models with one monolayer of Xe on the Cu(111) and Pt(111) surfaces, respectively. With the vdW interaction, the minimum separation between the Xe and the on-top Cu (Pt) atom is 3.20 (3.10) Å, compared to the experimental minimum of 3.60 (3.40) Å.…”
Section: Introductionmentioning
confidence: 99%